Using pipe-in-pipe systems for subsea pipeline vibration control - Bi, Kaiming; Hao, Hao (2016)
Pipe-in-pipe (PIP) systems are increasingly used in subsea pipeline applications due to their favourable thermal insulation capacity. Pipe-in-pipe systems consist of concentric inner and outer pipes, the inner pipe carries hydrocarbons and the outer pipe provides mechanical protection to withstand the external hydrostatic pressure. The annulus between the inner and outer pipes is either empty or filled with non-structural insulation material. Due to the special structural layout, optimized springs and dashpots can be installed in the annulus and the system can be made as a structure-tuned mass damper (TMD) system, which therefore has the potential to mitigate the pipeline vibrations induced by various sources. This paper proposes using pipe-in-pipe systems for the subsea pipeline vibration control. The simplification of the pipe-in-pipe system as a non-conventional structure-TMD system is firstly presented. The effectiveness of using pipe-in-pipe system to mitigate seismic induced vibration of a subsea pipeline with a free span is investigated through numerical simulations by examining the seismic responses of both the traditional and proposed pipe-in-pipe systems based on the detailed three dimensional (3D) numerical analyses. Two possible design options and the robustness of the proposed system for the pipeline vibration control are discussed. Numerical results show that the proposed pipe-in-pipe system can effectively suppress seismic induced vibrations of subsea pipelines without changing too much of the traditional design. Therefore it could be a cost-effective solution to mitigate pipe vibrations subjected to external dynamic loadings.